Metaphora and emotion used in summer's utterances as seen in jinn (2018) movie: socio-sematics approach - Seruni Adlan Dwiyanti (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri Sunan Kalijaga, 2021)
iim,1/irh,c.1